The Transparency Rules and Transparency Convention: A good start and model for broader reform in investor-state arbitration - Lise Johnson (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2014)
The 2014 UNCITRAL Transparency Rules and Transparency Convention are a good first step toward greater transparency in investor-state arbitrations. This Perspective encourages other institutions to follow suit and discusses how the Rules and Convention can be a model for broader reforms of the investment regime.
Keywords: 330